PENGARUH PENERAPAN KONSERVATISME AKUNTANSI DAN TINGKAT KEPEMILIKAN PADA KONFLIK BONDHOLDER-SHAREHOLDER DI BURSA EFEK INDONESIA - ADHIPUTRA, MADE WAHYU; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.05.TAHUN 2018, 2018)
This research is an empirical study aims to determine the effect of accounting conservatism and ownership level on bondholders-shareholders in Indonesia Stock Exchange. Populations of this study are firms listed in Indonesian Stock Exchange in 2014-2016. The sampling technique used is purposive sampling therefore there are 40 firms used in analysis. Independent variable of this study is accounting conservatism, institutional ownership dan management’s ownership, and dependent variable is bondholder-shareholder conflict. The samples were analyzed by using linear multiple regression tehnique, t-test for testing the hypothesis, and f-test for the feasibility model test with the five percent level of significant. It were tested with classic asumption test like normality test and heteroscedastisity test. Based on the analysis results is accounting conservatism affects bondholder-shareholder conflict. Institutional ownership does not effects bondholder-shareholder conflict and management’s ownership does not effects bondholder-shareholder conflict.